2022
DOI: 10.3390/pharmaceutics14061123
|View full text |Cite
|
Sign up to set email alerts
|

Nobiletin as a Neuroprotectant against NMDA Receptors: An In Silico Approach

Abstract: Excitotoxicity is a type of neurodegenerative disorder. It caused by excessive glutamate receptor activation, which leads to neuronal malfunction and fatality. The N-methyl-D-aspartate (NMDA) receptors are found in glutamatergic neurons, and their excessive activation is primarily responsible for excitotoxicity. They are activated by both glutamate binding and postsynaptic depolarization, facilitating Ca2+ entry upon activation. Therefore, they are now widely acknowledged as being essential targets for excitot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…In Figure 5b, glutamate and residues within the orthosteric binding pocket nearly overlapped, indicating an insignificant conformational change of the orthosteric binding pocket after PAM binds to NMDAR. Thr115, Arg120, Thr173, and Asp214 formed hydrogen bonds between glutamate and NMDAR, which is also consistent with the search results of Sadaf et al 32 For the NAM group, the situation is slightly different in that after the simulation, the position of glutamate has changed with a mild shift (Figure 6b), leading to the ligand−residue interaction free energy difference between with/without NAM structures. As glutamate is a small molecule, its flexibility in a comparatively big binding pocket is acceptable.…”
Section: Comparison Of the Orthosteric Binding Pocket In The Abl1supporting
confidence: 90%
“…In Figure 5b, glutamate and residues within the orthosteric binding pocket nearly overlapped, indicating an insignificant conformational change of the orthosteric binding pocket after PAM binds to NMDAR. Thr115, Arg120, Thr173, and Asp214 formed hydrogen bonds between glutamate and NMDAR, which is also consistent with the search results of Sadaf et al 32 For the NAM group, the situation is slightly different in that after the simulation, the position of glutamate has changed with a mild shift (Figure 6b), leading to the ligand−residue interaction free energy difference between with/without NAM structures. As glutamate is a small molecule, its flexibility in a comparatively big binding pocket is acceptable.…”
Section: Comparison Of the Orthosteric Binding Pocket In The Abl1supporting
confidence: 90%
“…The compounds filtered by pharmacophore models were further filtered by the “Filter by Lipinski and Veber Rules” module in DS2019. 23 The parameter of molecular weight was altered to 700.…”
Section: Methodsmentioning
confidence: 99%
“…The detailed results of ADME/pharmacokinetics prediction analysis of the six top-ranked phytochemicals of O. sanctum are shown in Supplementary Table S1. The Swiss-ADME analysis of the top-ranked phytochemicals of O. sanctum using the ESOL method [25] predicted all the six phytochemicals (Vicenin-2, Luteolin-7-O-glucuronide, Molludistin, Galuteolin, Vitexin, and rosmarinic acid) as soluble in water, whereas, the Ali method [26,27] predicted the three phytochemicals (Galuteolin, Luteolin-7-O-glucuronide, and rosmarinic acid,) as moderately soluble, and three phytochemicals (Molludistin, Vitexin, and Vicenin-2) as purely soluble in water (Table 2 and Supplementary Table S1). Moreover, on applying the Lipinski rule of 5, we found that, among the six phytochemicals, the physiochemical properties of two compounds (Molludistin and Rosmarinic acid) did not violate any criterion among the set criteria, whereas Vitexin violated only one criterion.…”
Section: Adme Analysismentioning
confidence: 99%